2008
DOI: 10.1063/1.2958275
|View full text |Cite
|
Sign up to set email alerts
|

Understanding quantum interference in coherent molecular conduction

Abstract: Theory and experiment examining electron transfer through molecules bound to electrodes are increasingly focused on quantities that are conceptually far removed from current chemical understanding. This presents challenges both for the design of interesting molecules for these devices and for the interpretation of experimental data by traditional chemical mechanisms. Here, the concept of electronic coupling from theories of intramolecular electron transfer is extended and applied in the scattering theory (Land… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

12
299
1

Year Published

2009
2009
2021
2021

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 262 publications
(312 citation statements)
references
References 38 publications
12
299
1
Order By: Relevance
“…It has been reported that destructive QI exists in benzene with the meta connectivity and is responsible for the observed reduction of conductance 16,20,28 , whereas for para and ortho connectivities, constructive QI should be observed 44,45 . The transmission coefficient calculations through junctions where the metal-ring connection is artificially blocked (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…It has been reported that destructive QI exists in benzene with the meta connectivity and is responsible for the observed reduction of conductance 16,20,28 , whereas for para and ortho connectivities, constructive QI should be observed 44,45 . The transmission coefficient calculations through junctions where the metal-ring connection is artificially blocked (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, the lack of hybridization of the orbitals with the electrodes greatly simplifies the analysis of the features in the transmission. 18 This is especially important for molecules, which are expected to exhibit interference effects.…”
Section: Discussionmentioning
confidence: 99%
“…Examples include systems where quantum interference plays a role. [17][18][19][20] This necessitates accurate quantum chemical modeling of the molecule, while the details of the electrodes may be less important to transport. Several approximations exist that trade sophistication for efficiency in the description of the electrodes, [21][22][23][24][25] but to the best of our knowledge, there have been no systematic studies of the quality of the results obtained with such approximations.…”
Section: Introductionmentioning
confidence: 99%
“…Solomon et al also confirmed that the long linearly conjugated molecule is more conductive than the short cross-conjugated one. 43 They attributed this observation to the alternate singledouble bond structure in linearly conjugated molecule. From these facts, we can propose that the electron transport should be more efficient in those conjugated chains with alternate double and single bonds, such as polyacetylene.…”
Section: The Electron Transport Pathwaymentioning
confidence: 99%